1978
DOI: 10.1136/bmj.2.6135.457
|View full text |Cite
|
Sign up to set email alerts
|

Stroke after acute myocardial infarction: relation to infarct size.

Abstract: Summary and conclusionsIn a consecutive series of 783 patients with acute myocardial infarction, 13 (17%) suffered a stroke. In all but one case the strokes occurred among the 255 patients whose peak creatine kinase (CK) concentrations fell in the upper third of the range of values (over 1160 IU/l, about eight times the upper limit of normal); the exception was a patient with a pre-existing ventricular aneurysm. The incidence of stroke in the patients with CK over 1160 IU/l was 4-7%, 24 times the incidence whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
5

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(36 citation statements)
references
References 6 publications
3
28
0
5
Order By: Relevance
“…Another factor associated with an increased risk of stroke is infarct size [7,11]. This was not evaluated in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor associated with an increased risk of stroke is infarct size [7,11]. This was not evaluated in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Previous studies have shown that anterior wall STEMI has higher risk of inhospital stroke. 14,19,20 Patients with anterior wall STEMI are more likely to have low ejection fraction, 21 and the incidence of left ventricular mural thrombus is higher, 22 which might account for the higher risk of stroke in those populations. The results of our study are generally in line with those previous reports, except for the absence of upstream use of GP IIb/IIIa inhibitors as a risk factor.…”
Section: Risk Factors For Stroke Complicating Pcimentioning
confidence: 99%
“…Los factores de riesgo más relacionados entre ambos eventos son edad avanzada, clase funcional de Killip, extensión del infarto y ubicación en pared anterior [6][7][8] . Destacamos un estudio de 20.768 pacientes hospitalizados por IAM, donde la incidencia de ACV isquémicos o hemorrágicos entre pacientes que recibieron heparina profiláctica y quienes no, no mostró diferencias significativas 6 .…”
Section: Discussionunclassified